Make it Pawfficial a campaign encouraging the support towards trap, neuter, and return (TNR) programs for urban feral cats - Dela Cruz, Nicolle Annre' S. (College of Fine Arts, University of the Philippines Diliman, 2018)
Cat lovers are known to care not just for their pets but even for the stray cats in their community. They give joy to these people and in turn people treat them as their unofficial pets. But because not everyone can adopt all these stray into their homes, they are left to breed in the wild and increase in numbers exponentially. Trapping, Neutering, and Returning (TNR) is the only sustainable, long-term solution to the feline overpopulation issue, and the most humane approach in tackling this problem. However, it is not yet adopted by most communities due to perceived lack of interest and funding. The campaign "Make it PAWFFICIAL" in partnership with Philippine Animal Welfare Society (PAWS) is meant to encourage people to go beyond taking care of street cats as playmates or stress relievers and instead donate directly to the TNR cause.